Search for sources of winter common wheat resistance to septoria (Zymoseptoria tritici) by field and laboratory methods - O. S. Kononenko; N. V. Shishkin; P. I. Kostylev; N. T. Kupreishvili (Зерновое хозяйство России, 2025)
In order to develop highly productive winter common wheat varieties, it is necessary to pay attention not only to the state of the agrophytocenosis, but also to include disease-resistant plants in the breeding process. One of the most common diseases in Russia, including the Rostov region, is septoria (Zymoseptoria tritici). Varieties and samples with several septoria resistant genes are of great importance for breeding. Therefore, it is necessary to search for breeding material resistant to Zymoseptoria tritici to develop new resistant winter common wheat varieties. The purpose of the current study was to identify septoria resistant winter common wheat varieties and samples using PCR diagnostics. The study was conducted at the FSBSI “Agricultural Research Center “Donskoy” (FSBSI “ARC “Donskoy”) in 2020–2022. Against the infectious background during the years of study, there were conducted the field estimation of 35 winter common wheat samples for Z. tritici resistance. The largest number of winter common wheat varieties resistant to Z. tritici with 14.4% damage was established in 2022, these were 5 varieties ‘Matriks’, ‘Univer’, ‘Krasa Dona’, ‘Gomer’ (Russia), ‘KVS-Emil’ (Germany). In 2020, only one variety ‘Astarta’ (Ukraine) showed resistance with 15–20 % damage. In 2021, there were identified 3 resistant varieties (8.6 %) ‘SO-911’ (France) with 10–15 % damage, ‘KVS-Emil’ (Germany) and ‘Batya’ (Russia) with 15–20 % damage. The screening of 35 winter common wheat samples has shown the presence of the dominant resistance gene Stb4 in the varieties ‘XE-9710’ (France), ‘Matriks’, ‘Krasa Dona’, ‘Volny Don’, ‘Univer’ (FSBSI “ARC “Donskoy”, Russia), ‘KWS-Emil’ (KWS Lochow GMBH, Germany). As a result, there have been identified the varieties ‘Matriks’, ‘Univer’, ‘KVS-Emil’, ‘XE-9710’, which showed themselves to be moderately resistant and stable over the years; the resistance of these varieties was also confirmed by laboratory methods. The identified varieties are recommended for further study and use in the breeding process.